State Income of "Goa, Daman and Diu" for the Year 1984-85 (Quick Estimates) - Planning Commission (Planning Commission, 1984)
The present Brochure on quick Estimates of State Income of the Union Territory of Goa, Daman and Diu for the year 1934-85 is the fifteenth in the series of annual papers on the subject being brought out since 1970-71. It presents the Estimates of the Net State Domestic Product (NSDP) of the Territory both at currant and constant prices (1970-71) for the year 1970-71 and 1980-81 to 1984-85. In compiling these Estimates, the methodology laid down by the Central Statistical Organisation has been used.
Directorate of Planning, Statistics and Evaluation, Goa, Daman and Diu